2015
DOI: 10.1245/s10434-015-4554-8
|View full text |Cite
|
Sign up to set email alerts
|

A Long Non-coding RNA Activated by Transforming Growth Factor-β is an Independent Prognostic Marker of Gastric Cancer

Abstract: LncRNA-ATB plays an important role in EMT to promote invasion and metastasis through the TGF-β/miR-200s/ZEB axis, resulting in a poor prognosis in GC. LncRNA-ATB is a novel biomarker of lncRNA, indicative of a poor prognosis in GC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 25 publications
2
76
0
Order By: Relevance
“…As its name suggests, LncRNA-ATB is induced by TGF-β in multiple cancer types, including breast, colorectal, gastric, and hepatocellular carcinoma [52][53][54][55]. LncRNA-ATB plays an essential role in both the early-stage invasion process and the late-stage colonization phase of metastasis in vivo [52].…”
Section: Lncrna-atbmentioning
confidence: 99%
“…As its name suggests, LncRNA-ATB is induced by TGF-β in multiple cancer types, including breast, colorectal, gastric, and hepatocellular carcinoma [52][53][54][55]. LncRNA-ATB plays an essential role in both the early-stage invasion process and the late-stage colonization phase of metastasis in vivo [52].…”
Section: Lncrna-atbmentioning
confidence: 99%
“…In recent years, lncRNA has become a new candidate in diagnosing cancer disease, explaining the pathogenesis and development mechanism of malignant tumors, and in predicting the prognosis and the treatment of the disease as the biological markers. Recently, it has been reported that lncRNA-ATB, a novel lncRNA activated by TGF-β, promotes the invasion of hepatoma cells through induction of EMT (12)(13)(14). However, the role of lncRNA-ATB in RCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with healthy controls and healthy coal miners, higher lncRNA-ATB expression had higher ORs of CWP after adjusted for the potential confounders. Similarly, Saito et al found that gastric cancer (GC) patients in the high lncRNA-ATB group had a significantly worse prognosis than patients in the low lncRNA-ATB group [26]. The elevated expression of lncRNA-ATB was associated with tumor stages, histological grade and distant metastasis in renal cell carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Qu et al reported that lncRNA-ATB was directly correlated with clinical endpoints (overall survival) and could serve as an independent prognosis maker for pancreatic cancer patients [15]. Saito et al showed that increased lncRNA-ATB expression was a significant prognostic for increased recurrence and decreased survival of GC patients [26]. Iguchi et al found that higher lncRNA-ATB was involved in the progression of CRC and was a novel indicator of poor prognosis in patients with CRC [14].…”
Section: Discussionmentioning
confidence: 99%